Student assistance in brazilian higher education: methods for evaluation and monitoring - Câmara, Kathiurcia Montovanelli Cazotti; Gomes, Vanielle Aparecida do Patrocinio; Freitas, Rodrigo Randow de; Nunes, Isabel Matos (Brazilian Journal of Production Engineering, 2022)
This article aims to carry out a study on publications that refer to the monitoring and evaluation of student assistance in Brazilian Higher Education. The SciELO, Web of Science and Google Scholar databases were used and a bibliometric and qualitative analysis was carried out on the selected articles. Among the main instruments and methods found that proposed to evaluate the impacts of the actions of student assistance programs, qualitative and documentary research, bibliographic reviews, research in databases, case studies using questionnaires, interviews semi-structured, content analysis, seeking to analyze the perception of benefited students, graduating students, and executing agents of the programs.
Keywords: Student Assistance; Higher Education; Bibliometrics